Burial ritual, agriculture, and craft production among Bronze Age pastoralists at Tasbas (Kazakhstan). (January 2015) - Doumani, Paula N.; Frachetti, Michael D.; Beardmore, Rebecca; Schmaus, Tekla M.; Spengler, Robert N.; Mar'yashev, Alexei N.
Abstract: This article presents new archaeological research on the ritual and domestic life of pastoralists at the Bronze Age campsite Tasbas, Kazakhstan. We reconstruct the hitherto unrecorded economy of high mountain pastoralists who lived at the site from the mid-3rd to early 1st millennium B.C. We argue that within the broad dynamics of mountain pastoralism there is local variability as shown through multi-season residence, farming, and craft production. In bringing together multiple data sets to address how the site was used we 1) show that ceramics were locally produced with similar manufacture technology across eight centuries — which breaks significantly from the canonical cultural history and large-scale migration paradigms that have defined the regional archaeology for decades; 2) identify a new tradition of cremation ritual (3rd millennium B.C.), and; 3) present the earliest evidence (3rd millennium B.C.) for the local use of domesticated grains and then farming (2nd millennium B.C.) in northern Central Asia. We provide a unique case study to bear on debates concerning the relationship between long-term regional stability and technological innovations among early central Eurasian pastoralists.